2019
DOI: 10.1097/md.0000000000017825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of number of medications and age on adherence to antihypertensive medications

Abstract: This study tried to investigate the effects of number of medications and age on antihypertensive medication adherence in a real-world setting using a nationwide representative cohort. We obtained data from the National Health Insurance Service-National Sample Cohort (NHIS-NSC) of Korea, which is a sample of 2.2% (N = 1,048,061) of total population (N = 46,605,433). Patients aged 20 years or older (N = 150,550) who took antihypertensive medications for at least 1 year were selected. Medication posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 42 publications
6
44
2
4
Order By: Relevance
“…The study findings indicate that patients below 65 had lower adherence. Although the association between age and adherence is mixed with some studies reporting an inverted U-shaped association, 54 our results are consistent with studies that report that medication adherence is positively associated with increasing age. [55][56][57][58] Potential reasons could include an increased disease burden with older adults as compared to younger adults which could lead to increased awareness of their overall health status, an increased perceived risk of hypertension, and a quicker acceptance of their diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study findings indicate that patients below 65 had lower adherence. Although the association between age and adherence is mixed with some studies reporting an inverted U-shaped association, 54 our results are consistent with studies that report that medication adherence is positively associated with increasing age. [55][56][57][58] Potential reasons could include an increased disease burden with older adults as compared to younger adults which could lead to increased awareness of their overall health status, an increased perceived risk of hypertension, and a quicker acceptance of their diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…[55][56][57][58] Potential reasons could include an increased disease burden with older adults as compared to younger adults which could lead to increased awareness of their overall health status, an increased perceived risk of hypertension, and a quicker acceptance of their diagnosis. 54,55,59 Further, male patients had a higher likelihood of being in the RD trajectory as compared to the adherent trajectory. Prior research has demonstrated a higher adherence among females as compared to males on anti-hypertensive treatment [60][61][62] which illustrates the need to explore sex-specific barriers to medication adherence among older adults on ACEI/ARBs.…”
Section: Discussionmentioning
confidence: 89%
“…Unsurprisingly, as the number of drugs prescribed to older adults increases, so too do issues with adherence. Increasing age is not necessarily a predictor of non-adherence, although adherence is more likely to be lowest in older age categories of older adults [81,82]. There is greater recognition that adherence is a complex health behaviour with multifaceted determinants [83], and as a result, careful thought is needed when planning how to resolve barriers to adherence.…”
Section: Prescribing In the Face Of Multimorbiditymentioning
confidence: 99%
“…31 Statistical analyses demonstrated similar findings in multiple studies regarding adherence and age, with higher adherence being associated with increased age. 19,36,37 This may be related to increased awareness of health status with older age; 38 however, the association between older age and adherence is not well understood. 37 Sex was not determined to be associated with adherence.…”
Section: Discussionmentioning
confidence: 99%